PENYULUHAN KESEHATAN DAN PENERAPAN SENAM ANTI STROKE PADA MASYARAKAT DESA GUMAYUN KECAMATAN DUKUHWARU KABUPATEN TEGAL - anisa oktiawati (Jurnal Pengabdian Mitra Masyarakat (JPMM), 2019)
Background: As we get older, many disorders or diseases whose prevalence increases, organ systems undergoing an aging process will be vulnerable to disease. One of the diseases often experienced by the elderly is hypertension. People with hypertension must get treatment properly. Moreover, treatment of risk factors or other comorbid conditions must also be carried out until obtaining the target therapy for each condition. The results of a preliminary study through interview on 20 patients with hypertension at RW 06 said they wanted to know more about hypertension and its dangers. 10 hypertension sufferers at RW 06 said they had been hospitalized because of hypertension until they had a mild stroke.Objective: It is expected that health education about hypertension and the application of anti-stroke exercises can control and reduce blood pressure for people with hypertension and will ultimately reduce the risk of stroke complications.Methods: Community service has been carried out, using promotive and preventive methods by community empowerment through the assistance of health cadres. The team in community service was D III Nursing Lecturer with some students and health cadres at RW 06 Gumayun Village, Dukuhwaru District, Tegal Regency.Results: From the evaluation results, it showed that the cadre and community members of RW 06 were very enthusiastic in participation of the extension activities from beginning to the end. From the results of questions and answers conducted by the moderator after the delivery of counseling materials, it can be ensured that most participants have understood about hypertension and they can feel that hypertension can cause complications. Anti-stroke gymnastics was carried out in order to achieve optimal welfare, by promoting and preventing the reduction in the incidence of stroke due to high blood pressure suffered by some people.Conclusion: The community service was attended by Cadres and Chairperson of RW 06 who were actively involved and gave satisfaction to the affected communities and increased community knowledge and ability in fulfilling healthy lifestyles, especially for controlling blood pressure in people with high blood pressure. It has made the fulfillment of higher education institutions. The community hopes that the activity can continually exist for those who need the attention of experts in their fields.Keywords: Hypertension, Gymnastics, Stroke